Reexamining the Notion of Wealth Management: Insights from the Qur'an and Hadith - Nurizal Ismail; Siti Aisyah (Tathawwur: Jurnal Ekonomi Pembangunan dan Keuangan Islam, 2023)
The Muslim population is expected to grow significantly by 26 per cent by 2030, reaching about 2.2 billion, a significant figure. Currently, the global Islamic finance market was valued at US$2.2 billion in 2021 and is expected to reach US$3.02 billion by 2027, exhibiting a Compound Annual Growth Rate (CAGR) of 10.2% during the period of 2022-2027. The demand for wealth management that is in line with Islamic principles is rapidly increasing. Islamic wealth management is a new and promising financial service industry that is attracting affluent individuals who want their assets managed in accordance with Islamic values and principles. It is important to note that Islamic wealth management is distinct from the Western conception of wealth management due to its distinct philosophical foundation. Hence, understanding the philosophical foundations of Islamic wealth management is crucial to effectively manage wealth from an Islamic perspective. The purpose of this paper is to redefine the contemporary concept of wealth management from an Islamic viewpoint, drawing insights from the Qur'an and Sunnah, and propose an Islamic framework for wealth management. The research findings indicate that Islamic wealth management, derived from the Qur'an and Hadith, centers around the concept of Tawhīd as the central pillar and the adherence to Shari'ah as the guiding law for Muslims. The process of Islamic wealth management encompasses two key aspects: wealth creation and spending that consists of wealth accumulation, protection, and distribution. The creation of wealth is closely linked to the fulfillment of the objective of infāq (spending), which aims to promote maqashid shari'ah and advance justice and well-being in order to achieve falah (success and prosperity in the world and hereafter).